STUDY OF ICONOGRAPHY AND ISLAMIC CULTURAL EXPRESSION AT THE GRAVE OF MARHUM PEKAN IN PEKANBARU - Edi Prawito (PT. Jurnal Center Indonesia Publisher, 2026)
This study examines the visual symbols and cultural values ​​contained in the Marhum Pekan Tomb, one of the historical sites inherited from the Siak Sri Indrapura Sultanate which is the cultural identity of Pekanbaru City. The purpose of this study is to reveal the meaning, philosophical values, and forms of acculturation of Islamic culture with local Malay traditions represented through the physical form and ornamentation of the tomb. This study uses a qualitative descriptive method with Erwin Panofsky's iconographic approach which includes three stages of analysis, namely pre-iconography, iconography, and iconology. Data sources were obtained through field observations, in-depth interviews, as well as literature and documentation reviews. The results of the study show that visually (pre-iconography), the Marhum Pekan Tomb displays the architectural characteristics of the Selaso Jatuh Kembar House, the use of Malay regalia, stepped jirat forms, and headstones with gender-differentiating shapes, all of which are a blend of local and Islamic culture. Based on the iconographic analysis, all ornaments in the form of plant and flower motifs contain symbolic meanings of purity, fragrant names, good deeds, and obedience to Islamic teachings that prohibit the depiction of living creatures. Meanwhile, iconological analysis reveals the fundamental meaning that this tomb complex is a tangible manifestation of the Malay people's philosophy of life, namely